Suramin exposure alters cellular metabolism and mitochondrial energy production in African trypanosomes - Zoltner, Martin; Campagnaro, Gustavo D; Taleva, Gergana; Burrell, Alana; Cerone, Michela; Leung, Ka-Fai; Achcar, Fiona; Horn, David; Vaughan, Sue; Gadelha, Catarina; Zíková, Alena; Barrett, Michael P; et al. (The Journal of biological chemistry, 2020)
Introduced about a century ago, suramin remains a frontline drug for the management of early-stage East African trypanosomiasis (sleeping sickness). Cellular entry into the causative agent, the protozoan parasite Trypanosoma brucei, occurs through receptor-mediated endocytosis involving the parasite's invariant surface glycoprotein 75 (ISG75), followed by transport into the cytosol via a lysosomal transporter. The molecular basis of the trypanocidal activity of suramin remains unclear, but some evidence suggests broad, but specific, impacts on trypanosome metabolism (i.e. polypharmacology). Here we observed that suramin is rapidly accumulated in trypanosome cells proportionally to ISG75 abundance. Although we found little evidence that suramin disrupts glycolytic or glycosomal pathways, we noted increased mitochondrial ATP production, but a net decrease in cellular ATP levels. Metabolomics highlighted additional impacts on mitochondrial metabolism, including partial Krebs' cycle activation and significant accumulation of pyruvate, corroborated by increased expression of mitochondrial enzymes and transporters. Significantly, the vast majority of suramin-induced proteins were normally more abundant in the insect forms compared with the blood stage of the parasite, including several proteins associated with differentiation. We conclude that suramin has multiple and complex effects on trypanosomes, but unexpectedly partially activates mitochondrial ATP-generating activity. We propose that despite apparent compensatory mechanisms in drug-challenged cells, the suramin-induced collapse of cellular ATP ultimately leads to trypanosome cell death.
Keywords: energetický metabolismus; polypharmacology; Mitochondria; adenosintrifosfát; drug mechanisms; Proton-Translocating ATPases; drug action; parasite metabolism; proteom; Flagella; Proline; metabolomics; suramin; Suramin; proteomics; prolin; Pyruvic Acid; protozoální proteiny; energy homeostasis; flagella; Trypanosoma brucei brucei; Trypanosoma brucei; glycosomes; molekulární modely; trypanosome; Models, Molecular; kyselina pyrohroznová; Energy Metabolism; sleeping sickness; differentiation; Metabolome; Adenosine Triphosphate; membránový potenciál mitochondrií; mikrotělíska; Glycolysis; Microbodies; Protozoan Proteins; metabolom; Proteome; protonové ATPasy; glykolýza; Membrane Potential, Mitochondrial; mitochondrie